Decolonising curriculum in education: continuing proclamations and provocations (UCL Press, 2022)
There is no denying the importance and increased significance of interest in decolonisation in education and the wider social sciences. This article aims to bring a continuing contribution to an evolving and important discussion. The methodology of this work allows a range of academics from different cultural contexts to voice their decolonising proclamations. The authors of the article are a combination of White, Black, Asian and mixed-race academic researchers in higher education who have come together to proclaim their viewpoints. They draw upon their research and apply professional practice in relation to differing aspects of generally decolonising education and specifically decolonising curricula. As a group, we believe that the notion of decolonising applies to all sections of education - not only to primary schools, but also to nurseries, secondary schools, colleges and universities. We hope this article will encourage more research, advocacy and action within education and interdisciplinary contexts into the complexity of decolonising the curriculum.